Two Cu(i) coordination polymers based on a new benzimidazolyl-tetrazolyl heterotopic ligand for visible-light-driven photocatalytic dye degradation. Issue 3 (9th December 2022) - Tang, Ping; Xie, Xue-Xian; Huang, Zi-Yuan; Kuang, Zhi-Yang; Cai, Song-Liang; Zhang, Wei-Guang; Zheng, Sheng-Run
Abstract : Two Cu(i ) CPs based on a new heterotopic tripodal ligand were constructed and their visible-light-driven photocatalytic performance were studied. Abstract : Two Cu(i ) coordination polymers (CPs), namely, [Cu I (DBPT)(H2 O)] n (HDBPT = 3, 5-di((1 H -benzeimidazol-yl)phenyl)-2 H -tetrazole, CP 1 ) and [Cu I (DBPT)·DMF] n (CP 2 ), were constructed based on a new N-containing heterotopic triangular ligand. CP 1 is a 2D network consisting of binuclear secondary building units (SBUs). The 2D layers are connected by strong hydrogen bonds to form a 3D supramolecular framework. CP 2 possesses a 3D framework based on binuclear SBUs and features a (3, 6)-connected rtl topology. Both CP 1 and CP 2 have high stability in water in the pH range from 3–13 and exhibit energy band gaps of 2.70 and 2.79 eV, respectively, which indicate their possibility in visible-light-driven photocatalysis. The photocatalytic results show that both CP 1 and CP 2 display good activity for MLB degradation in the presence of H2 O2 as an oxidant under visible light irradiation. A mechanistic investigation indicated that the photogenerated holes trapped by Cu(i ) generate Cu(ii ). Cu(ii ) may be involved in a Fenton-like CuI/CuII redox reaction to generate ˙OH. Thus, holes and ˙OH contribute to the degradation of MLB. In addition, the degradation product of MLB was further studied by LC-MS, which indicates that MLB is almost degraded to small molecules.